Characteristics of Aerococcus viridans isolated from porcine fetuses in Korean farms. Issue 4 (24th February 2021) - Nguyen, Van Giap; Kim, Cheong Ung; Do, Hai‐Quynh; Shin, Sook; Jang, Keum Chan; Park, Yong Ho; Park, Bong Kyun; Chung, Hee Chun
Abstract: Swine abortion caused by viruses as well as bacteria has caused many economic losses in domestic farms over the years; however, bacterial abortion has not yet been studied in Korea. Several bacterial species were isolated from aborted fetuses ( n = 103) for which the cause of death was not viral abortion. Among them, we focused on Aerococcus viridans, which had the highest positive rate within three provinces (Gangwon, Jeonnam and Gyeongnam). A total of 16 isolates were identified as A. viridans by matrix‐assisted laser desorption ionization‐time of flight mass spectrometry (MALDI‐TOF MS), and 13 were characterized by both antibiotic resistance and 16S rRNA gene analysis. Based on antibiotic susceptibility testing result, eight antimicrobials could not effectively eliminate the present isolation (more than 40% of isolates can resist these antibiotics), while all except two strains were susceptible to trimethoprim/sulfamethoxazole. Molecular analysis indicated genetic variation among these strains. This study is the first report detecting A. viridans from aborted fetuses in Korean domestic farms. Abstract : This is the first description of the prevalence of A. viridans in Korean swine herds and the fetuses demonstrate the considerable prevalence of A. viridans in Korea.